Análise do fluxo de descarte de resíduos de equipamentos eletroeletrônicos na região de Sorocaba - Cardoso, Felipe Flores Martins (Universidade Federal de São Carlos, 2023)
The disposal of waste electrical and electronic equipment is a highly important topic that has gained increasing relevance in recent years due to its impact on the environment from a sustainability perspective. The purpose of this study is to analyze the flow of waste electrical and electronic equipment disposal in the Sorocaba region through the perspectives of the population, companies, and cooperatives. Data was collected through the use of forms, and a comparison was made between this data and the information found in the literature. The literature was classified using the SWOT methodology, which highlighted the strengths, weaknesses, and opportunities. The main results of the study include the significant gap between the generation of waste electrical and electronic equipment and its proper treatment, as well as opportunities to minimize environmental impacts through awareness. Additionally, this study aims to facilitate the development of plans for the evolution of a sustainable circular economy and the enhancement of waste electrical and electronic equipment disposal issues, while reinforcing the association of Brazilian legislation with the Sustainable Development Goals (SDG).
Understanding the waste disposal flow of electronics in the region of Sorocaba through field research and literature review.
Keywords: Descarte de Resíduos de Equipamentos Eletroeletrônicos; Descarte de REEE; SWOT; Disposal of Waste Electrical and Electronic Equipment; WEEE Disposal; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO